The identification and characterization of a plant height and grain length related gene hfr131 in rice - Lan, Dengyong; Cao, Liming; Liu, Mingyu; Ma, Fuying; Yan, Peiwen; Zhang, Xinwei; Hu, Jian; Niu, Fuan; He, Shicong; Cui, Jinhao; Yuan, Xinyu; Yang, Jinshui; et al. (Frontiers in Plant Science, 2023)
Plant height and grain size are important agronomic traits affecting rice yield. Various plant hormones participate in the regulation of plant height and grain size in rice. However, how these hormones cooperate to regulate plant height and grain size is poorly understood. In this study, we identified a brassinosteroid-related gene, hfr131, from an introgression line constructed using Oryza longistaminata, that caused brassinosteroid insensitivity and reduced plant height and grain length in rice. Further study showed that hfr131 is a new allele of OsBRI1 with a single-nucleotide polymorphism (G to A) in the coding region, leading to a T988I conversion at a conserved site of the kinase domain. An auxin response factor, OsARF17, could bind to the promoter region of HFR131 and positively regulated HFR131 expression, thereby regulating the plant height and grain length, and influencing brassinosteroid sensitivity. Haplotype analysis showed that the consociation of OsAFR17Hap1/HFR131Hap6 conferred an increase in grain length. Overall, this study identified hfr131 as a new allele of OsBRI1 that regulates plant height and grain length in rice, revealed that brassinosteroid and auxin might coordinate through OsARF17–HFR131 interaction, and provided a potential breeding target for improvement of rice yield.